Pengembangan Media Mini Shadow Puppet dengan Metode Story Telling untuk Mengembangkan Prososial Anak di TK - Erik, Erik; Sari Dewi, Mela (THUFULA, 2021)
Mini Shadow Puppet Media Development With Storytelling Method To Develop Prosocial Children In Linggarjati Kindergarten. Early Childhood Education Teacher Education Study Program (PGPAUD) Muhammadiyah Kuningan College of Teacher Training and Education (STKIP). The purpose of this study was to determine the increase in the ability of children’s prosocial behavior in group B students at Linggajati Kindergarten through the use of Mini Shadow Puppet learning media. The method used in this study is research & development (RnD) where researchers develop learning media by adopting research steps from Borg and Gall which are simplified into three stages, including: data collection stage, design stage, validation stages trials. The subjects of this study were children of group B of the Linggajati Kindergarten. The results of this study were the Mini Shadow Puppet very suitable to be used as a medium for early childhood learning, because of its attractive design and proportional size is able to focus the child’s attention.